Numbers that tell a story: Measuring the impact of open access books - Emery, Christina; Lucraft, Mithu; Morka, Agata; Prandi, Matteo; Pyne, Ros (Septentrio Conference Series, 2018)
Open access book publishing is gaining momentum, with more than 10,000 titles published worldwide. But compared to the overall number of academic books that are produced, this is still a small percentage. With much research on the benefits to society from open access publication, what can we do to encourage more book authors to choose open access? Springer Nature is a leading academic book publisher – to date, we have published more than 550 open access books since launching OA book options in 2012. Feedback from our OA book authors has shown that metrics are important to them, as the data helps demonstrate the impact of their research to funders, and also supports conversations with their institutions for career progression. However, as highlighted in our white paper ‘The OA effect: How does open access affect the usage of scholarly books?’, some authors feel that there is a lack of information around metrics and book performance. This information may be critically important in helping authors consider the benefits of choosing to publish their book open access. Authors also state that one of the main obstacles to publishing more OA books through the gold route is funding; access to which varies globally and by discipline – a central theme that emerged at our researcher event during Academic Book Week 2018. Meanwhile, funders interviewed for ‘The OA Effect’ told us that they were keen to understand the impact of the OA books they had supported, but few had actually done so; many commented on the difficulties of measuring the impact of research. In light of these findings, in 2018 we piloted a new “impact report”, based on metrics for an individual funder of OA books. The outcomes of this pilot impact report project will help the scholarly communications community to better understand how publishers can inform funders, authors and their institutions about the impact of their research, and on a wider scale. What are the challenges of sharing the benefits of OA book publishing with researchers across different disciplines, and how can we overcome these challenges? Our poster shows excerpts from the pilot impact report, quotes from authors and funders about research impact, and considers next steps.